Pengaruh Terapi Bermain Squishy Terhadap Penurunan Kecemasan Anak Usia Prasekolah (3-6 Tahun) Yang Mengalami Hospitalisasi di Rumah Sakit Rizani Paiton Probolinggo - Mimik Aminatur Rohmah; Rizka Yunita; Nafolion Nur Rahmat (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hospitalization is a disruptive experience for children that can also induce anxiety. Generally, the reactions of children undergoing inpatient care are anxiety, crying, and restlessness. Play therapy can help distract children from pain and provide relaxation. This study aims to determine the effect of squishy toy play therapy on reducing anxiety in preschool-aged children (3-6 years old) undergoing hospitalization. This study employs a Pre-Experimental method with a One Group Pre-Post Test Design. The population for this research is 200 children each month. The sample consists of 80 respondents who are preschool-aged (3-6 years old) and have been admitted to Rizani Paiton Probolinggo Hospital. The sampling technique used is accidental sampling. Data management involves processes such as Editing, Coding, Scoring, and Tabulating, and the data are analyzed using the Wilcoxon test.Top of FormBottom of Form The results of this study show that the average anxiety score before the squishy toy play therapy was 2.54. The average anxiety score after the therapy was 1.56. The analysis using the Wilcoxon test indicates that there is an effect of squishy toy play therapy on reducing anxiety in preschool-aged children (3-6 years old) undergoing hospitalization, with a p-value of 0.000. Squishy play therapy is carried out twice a day for three consecutive days, squishy play therapy is suitable for preschool children because this therapy is easy to do, does not require a lot of facilities and takes a short time. Suggestions for further researchers observe parents and closest people as one of the factors that influence the effectiveness of squishy play therapy.